ANALISIS KONSEP HUBUNGAN TEGANGAN, BEBAN, ARUS DAN HAMBATAN PADA RANGKAIAN MENGGUNAKAN VIRTUAL LAB - Febrianti, Dilla Ayu; Rustiani, Eka Astria; Putri, Elmira Primasari; Fikri, Fikri; Khalidurrahman, Ahmad Fauzan; Ramawati, Devi (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2023)
A virtual lab, also known as an online or remote lab, is a web-based educational tool simulating actual laboratory experiments and experiences in a digital environment. This virtual laboratory aims to provide students and researchers with a realistic and interactive learning experience without needing physical laboratory equipment and resources. This study aims to prove that the amount of electric current is inversely proportional to resistance or resistance, as Ohm's law applies by using a virtual lab. The approach used in this study is a quantitative approach to the experimental method. From this practicum, under Ohm's law, it is proven that the relationship between voltage and current is directly proportional. The greater the voltage, the greater the current, and vice versa. And also, the relationship between resistance and current is inversely proportional. The more excellent the resistance or resistance of a conductor, the smaller the current that will flow through the conductor. Conversely, the smaller the resistance of a conductor, the greater the current that will flow through the conductor. Therefore, the virtual lab can be used as an additional tool to increase students' understanding of Ohm's law and provide students with practical, engaging, and safe learning experiences. As technology advances, virtual laboratories are expected to become more sophisticated and blend with modern education.